Pharmacotherapy of gastrointestinal disorders in the elderly - TAZEGÜL, GÖKHAN (TÜRKİYE KLİNİKLERİ, 2023)
Drugs used in gastrointestinal (GI) disorders hold particular significance in the clinical care of the elderly due to several factors beyond the well-documented pharmacokinetic and pharmacodynamic changes associated with aging. These factors are essential to consider when prescribing, dosing, and monitoring the use of GI agents in older adults. Pharmacotherapy of GI disorders requires a holistic approach that considers the clinical complexity of older adults, their multiple medication regimens, nutritional needs, safety concerns, and the balance between managing GI conditions and maintaining overall health. A patient-centered and multidisciplinary approach is necessary for optimizing the use of these drugs in older adults while minimizing potential adverse effects. In this review, we covered the most commonly prescribed and critical drugs that are used in the treatment of GI disorders in the elderly population, aiming to inform and guide pharmacotherapy decisions in clinical practice.

Gastrointestinal sistem (GİS) hastalıklarında kullanılan ilaçlar, yaşlanma süreciyle ilişkili iyi bilinen farmakokinetik ve farmakodinamik değişikliklerin ötesinde bazı faktörler nedeniyle yaşlı hastaların klinik bakımında özel bir öneme sahiptir. Bu faktörler, yaşlı erişkinlerde GİS ilaçlarının reçete edilmesi, dozunun belirlenmesi ve kullanımının takibi sırasında dikkate alınmalıdır. GİS hastalıklarının farmakolojik tedavisi, yaşlı bireylerdeki klinik tablonun karmaşıklığını, çoklu ilaç rejimlerini, beslenme ihtiyaçlarını, ilaç güvenliliği ile ilgili endişeleri ve GİS hastalıklarının yönetilmesi ile genel sağlığın korunması arasındaki dengeyi göz önünde bulunduran bütüncül bir yaklaşım gerektirir. Bu ilaçların yaşlı hastalarda kullanımını optimize etmek ve potansiyel advers etkileri minimize etmek için hasta-merkezli ve multidisipliner bir yaklaşım benimsenmelidir. Bu derlemede, yaşlı nüfusta GİS bozukluklarının tedavisinde kullanılan en yaygın reçete edilen ve kritik ilaçları ele aldık ve klinik uygulamada ilaç tedavisi ile ilgili kararlara bilgi ve rehberlik sunmayı amaçladık.
Yaşlılarda gastrointestinal bozuklukların farmakoterapisi
Keywords: Proton pump inhibitors; histamine H2 antagonists; laxatives; antidiarrheals; antiemetics; Proton pompası inhibitörleri; histamin H2 antagonistleri; laksatifler; antidiyareikler; antiemetikler